Headaches in Traumatic Brain Injury: Improvement Over Time, Associations With Quality of Life, and Impact of Migraine-Type Headaches. Issue 2 (26th March 2023) - Flynn, Spencer; Moore, Brian; van der Merwe, Andre J.; Moses, Anita; Lo, Jessica; Shahim, Pashtun; Chan, Leighton
Abstract : Objective: To describe headache characteristics over time in patients with traumatic brain injury (TBI). Setting: Patients enrolled and followed at the National Institutes of Health Clinical Center between 2011 and 2020. Participants: There were 147 patients with TBI, with 74 mild TBI (mTBI), 49 moderate (modTBI), 24 severe (sTBI), and 20 individuals without brain injury (IWBIs). Design: Regular surveys of headache characteristics in patients with TBI were conducted. Patients were enrolled as early as 30 days post-injury and followed up to 5 years, for 419 total visits and 80 patients with multiple return visits. Main Measures: Surveys of headache characteristics, including headache severity, were measured on a 0- to 10-point Likert scale and headache frequency quantified as headaches per month. Patients with migraine-type headaches ( n = 39) were identified by a clinician-administered tool. Functional outcomes were measured using the Glasgow Outcome Scale-Extended (GOS-E) and quality of life by the Satisfaction with Life Scale (SWLS) and the 36-item Short Form Survey (SF-36). Results: At their initial visit, patients with TBI had more severe and frequent headaches than IWBIs (median 5 vs 2.5, P < .001; median 2 vs 0.2, P < .001), as did patients with mTBI compared with modTBI/sTBI (all P ≤ .01). Migraines were associated with lower SWLS and SF-36 scores. Migraines and young age were associated with higher headache severity and frequency across time points. Longitudinally, time post-injury correlated with improvement in headache severity and frequency without differences by injury severity. However, time post-injury did not correlate with improvement in headache characteristics in a patient subgroup with moderate/severe headaches. Conclusion: Our findings suggest that patients with mild, moderate, or severe TBI see improvement in headaches over time. However, patients should be counseled that improvement is modest and seen more in patients with milder headache symptoms. Patients with migraine headaches in particular are at risk for worse headache characteristics with greater impact on quality of life.